2022
DOI: 10.3389/fnagi.2022.904194
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Task Performance in Older Adults With and Without Idiopathic Normal Pressure Hydrocephalus

Abstract: Two of the main features of idiopathic normal pressure hydrocephalus (iNPH) are disturbed gait and cognition. These features are typically investigated separately, but here we combined walking with a cognitive task to investigate if older adults with iNPH were more susceptible to dual-task interference on walking than those without iNPH. In total, 95 individuals from the general population participated in our study. Of these, 20 were classified as Possible iNPH (median [interquartile range, IQR] 80 years [75–8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Our results showing worsened declarative memory is in line with other studies highlighting poor declarative memory in iNPH [ 19 , 41 ]. One example of memory impairment in iNPH is having to stop walking while recalling a recent event [ 32 ]. It is conceivable that the reduced memory performance in iNPH is related to the widening of the temporal horns (TH).…”
Section: Discussionmentioning
confidence: 99%
“…Our results showing worsened declarative memory is in line with other studies highlighting poor declarative memory in iNPH [ 19 , 41 ]. One example of memory impairment in iNPH is having to stop walking while recalling a recent event [ 32 ]. It is conceivable that the reduced memory performance in iNPH is related to the widening of the temporal horns (TH).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies emphasized the importance of examining dual task performance during evaluation of shunt candidacy in NPH during CSF tap test 16 , 27 , 28 . Other studies revealed that the evaluation of gait performance during single tasks is sufficient 15 , 29 . In line with this, the present results reveal a good to excellent classification accuracy across all examined conditions with highest mean AUC values for preferred walking and walking with a motoric dual tasking.…”
Section: Discussionmentioning
confidence: 99%
“…One example of memory impairment in iNPH is having to stop walking while recalling a recent event [32].…”
Section: Discussionmentioning
confidence: 99%
“…The participants were recruited from an epidemiological study on iNPH among inhabitants 65 years or older in a northern region of Sweden [4,7,[29][30][31][32][33]. Out of the original 168 participants at baseline in 2014/15, 127 participated at follow-up in 2016/17, of which 104 in the present study.…”
Section: Study Participantsmentioning
confidence: 99%